EXPLORING SYSTEMATIC GENDER DISCRIMINATION IN HOLLYWOOD THROUGH ENGLISH LITERATURE: A POST-FEMINIST ANALYSIS OF THE SEVEN HUSBANDS OF EVELYN HUGO - Shafa Nabila; Imas Istiani (Universitas PGRI Palembang, 2026)
This study explores systematic gender discrimination in the Hollywood entertainment industry through a post-feminist analysis of The Seven Husbands of Evelyn Hugo (2017) by Taylor Jenkins Reid. Despite increasing female participation in the industry, women continue to face structural inequalities, including objectification, limited career opportunities, and unequal power relations. Drawing on Angela McRobbie’s post-feminist theory, this research examines how female identity, empowerment, and gender bias are represented through the character of Evelyn Hugo. Using a qualitative descriptive method, the study analyzes Evelyn’s experiences as she navigates a male-dominated entertainment industry. The findings reveal that Evelyn’s success is achieved not by overcoming systemic barriers entirely but by strategically negotiating the constraints imposed by patriarchal structures. Her experiences demonstrate that empowerment within a post-feminist context often requires conformity to industry expectations and personal sacrifices related to identity, relationships, and self-expression. Furthermore, the analysis highlights how male-dominated power structures continue to shape women’s professional and personal lives. The study concludes that gender discrimination remains deeply embedded in Hollywood, despite narratives of progress and female empowerment.